2007
DOI: 10.1177/0883073807307083
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus-Induced Seizures in Childhood

Abstract: Rotavirus infection is a frequent cause of gastroenteritis in children and accounts for significant morbidity and mortality, especially in the developing world. Less well recognized is the association of rotavirus-induced central nervous system dysfunction, which has been associated with seizure, encephalopathy, and death. Symptoms may vary widely, however, and children can experience short afebrile convulsions as the only manifestation of rotavirus encephalopathy. We report 4 further cases of rotavirus-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 23 publications
1
45
0
1
Order By: Relevance
“…This finding seems to indicate that, in terms of febrile seizures (FS), an immature CNS may favour the occurrence of CwG. 26 Moreover, although some cases have been reported in Europe 17,27 and America, 18,21,28,29 CwG has been more frequently described in East Asian countries, mainly in Japan, South Korea, Taiwan and Hong Kong where it occurs in approximately 1% of all AGE cases. 8e16 This finding suggests that the genetic characteristics of the host may play a role in the development of CwG.…”
Section: The Epidemiology and Pathogenesis Of Cwgmentioning
confidence: 94%
“…This finding seems to indicate that, in terms of febrile seizures (FS), an immature CNS may favour the occurrence of CwG. 26 Moreover, although some cases have been reported in Europe 17,27 and America, 18,21,28,29 CwG has been more frequently described in East Asian countries, mainly in Japan, South Korea, Taiwan and Hong Kong where it occurs in approximately 1% of all AGE cases. 8e16 This finding suggests that the genetic characteristics of the host may play a role in the development of CwG.…”
Section: The Epidemiology and Pathogenesis Of Cwgmentioning
confidence: 94%
“…Furthermore, 3 out of 5 RV-infection associated cases in our study had afebrile seizures. DiFazio et al [20] also reported the children could experience afebrile convulsions as the only manifestation of RV encephalopathy.…”
Section: Etiological Pathogensmentioning
confidence: 95%
“…Chronic systemic rotavirus infection associated with hepatitis and renal disease has been reported on multiple occasions in children with severe combined immunodeficiency (24). Extraintestinal manifestations of RV infection, like mild hepatitis, are very common (31), while convulsions (associated with viral antigen in spinal fluid) occur sporadically (16,41). Modulation of the extent of systemic viral infection and its associated clinical sequelae is likely to be one of the effector functions of IgM ϩ mBc.…”
Section: Discussionmentioning
confidence: 99%